Hubungan Kecerdasan Emosional dan Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Kayla Hajar Zahira; Nensi Desiana Purnamasari; Dinda Kestu Anayanti; Nining Setyaningsih; Budi Murtiyasa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Students’ mathematics learning outcomes are influenced not only by academic ability but also by other factors such as emotional intelligence and learning motivation. However, these two factors are often overlooked in the mathematics learning process in schools. This study aims to investigate the relationship between emotional intelligence and learning motivation, examining both partial and simultaneous effects on students’ mathematics learning outcomes. A correlational method was used in this study, employing a quantitative approach. Data collection techniques included a questionnaire to measure emotional intelligence and learning motivation, as well as documentation to obtain data on students’ mathematics learning outcomes. The instrument consisted of a questionnaire using a 1–4 Likert scale. The results indicate that there is a relationship between emotional intelligence and mathematics learning outcomes, a relationship between learning motivation and mathematics learning outcomes, and a simultaneous relationship between both factors and students’ mathematics learning outcomes. This study implies that teachers and schools are expected to pay closer attention to students’ emotional and motivational aspects in mathematics learning to improve learning outcomes.